2004
DOI: 10.1002/pen.20233
|View full text |Cite
|
Sign up to set email alerts
|

In situ generated diphenylsiloxane‐polyimide adduct‐based nanocomposites

Abstract: Arylsiloxane was incorporated into polyimide (PI) via electronic interaction with polyamic acid (PAA)/PI, and a wide spectrum of properties were evaluated for different compositions. The samples prepared with relatively low concentrations (0.0001–0.1%) of oligomers showed unusual synergism, which is attributed to the generation of nanostructures dispersed in the continuous PI matrix. The incorporation of siloxane with bulky phenyl groups contributed to enhanced thermal stability as determined by thermogravimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…8. Earlier studies [11,18,19] demonstrated the effect of incorporating low concentration of organic and inorganic crosslinker in PI matrix resulting in reduced absorption characteristics. A very significant reduction (70%) in water absorption was observed in MPI-5.…”
Section: Water Absorption Studies Of Metallopolyimide Filmsmentioning
confidence: 99%
“…8. Earlier studies [11,18,19] demonstrated the effect of incorporating low concentration of organic and inorganic crosslinker in PI matrix resulting in reduced absorption characteristics. A very significant reduction (70%) in water absorption was observed in MPI-5.…”
Section: Water Absorption Studies Of Metallopolyimide Filmsmentioning
confidence: 99%
“…The control of inorganic particle size and dispersion of particles within organic matrices using solution synthesis processes is currently a frontier field of research with far‐reaching implications for new technologies 5–7. In previous studies of hybrid composites it was demonstrated that the properties of the polymer matrix are strongly influenced by the presence of inorganic materials 8–11…”
Section: Introductionmentioning
confidence: 99%